Numerical study on the effect of thermal pad on enhancing interfacial heat transfer considering thermal contact resistance - Xing-Jie Ren; Qing-Feng Tang; Heng Zhang; Jian-Rong Zhang; Mu Du; Wen-Quan Tao (Case Studies in Thermal Engineering, 2023)
In this paper, a 3D numerical model was established to investigate the effect of thermal pad on enhancing heat transfer of rough contact interfaces. The model is a sandwich structure and it includes chip, thermal pad and heat sink. The results indicate that the elastic modulus of the thermal pad can affect the actual contact area of rough contact interfaces, which further affects interfacial heat transfer. Besides, it is the through-plane thermal conductivity of the thermal pad that affects the heat dissipation of the chip, and increasing through-plane thermal conductivity of the thermal pad is more effective than increasing the clamping pressure for heat dissipation. Furthermore, if thermal conductivity of the thermal pad is low, the efficiency of simply increasing convective heat transfer coefficient at the side of the heat sink is limited for heat dissipation. The study also investigates thermal contact resistances among thermal pad, chip and heat sink. The results indicate that thermal contact resistance is influenced by material properties, and thermal contact resistance accounts for 2.2%–45.85% of total thermal resistance for the studied cases of this paper. The model was validated by experimental results and can be acceptable to study the heat dissipation of the sandwich structure with rough contacts.